Pengaruh Kualitas Produk Tabungan dan Kualitas Pelayanan Terhadap Kepuasan Nasabah, Berdampak Pada Loyalitas Nasabah Tabungan Tanda 360 Bank OCBC NISP - Laili Septiana; Cicih Ratnasih (Jurnal Manajemen FE-UB, 2021)
The data used in this study are primary data taken from the results of questionnaireresponses by customers of Bank OCBC NISP Cab Plaza Jababeka Cikarang. The data processingmethod uses the path analysis method with the help of the SPSS version 20 analysis tool.Statistical testing in this study uses the goodness of fit test.The results show that product quality and service quality have a positive influence directlyor indirectly through customer satisfaction which has an impact on customer loyalty.Keywords: Product Quality, Service Quality, Customer Satisfaction, Customer Loyalty.